Minersville, Cloud County - Martin, Sylvia (Kansas State University, The Chapman Center for Rural Studies, 2017)
This study examines the town of Minersville in Sibley Township, Cloud County, Kansas. It lasted from 1870 to 1945. I used maps, newspaper articles and fieldwork.
Sylvia Martin, “Minersville, Cloud County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/205.
Keywords: Cloud County; Minersville; Republic County; Scottish; Sibley Township; mining